(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article examines, through an analytical approach, the theoretical foundations, didactic potential, and practical possibilities of electronic textbooks in developing the professional competence of future preschool educators. Within the framework of the study, the influence of electronic textbooks on the cognitive, methodological, digital, and reflective components of professional training is clarified, and their functional significance in the preparation of students in preschool education is substantiated. The advantages, practical opportunities, and existing challenges associated with the use of electronic textbooks are also considered as interrelated pedagogical factors. The findings demonstrate that electronic textbooks constitute an important means of activating the independent learning activity of future educators, developing their methodological thinking, enhancing digital literacy, and strengthening the integration of theory and practice. The article also offers relevant conclusions for the scientific and methodological improvement of the processes of designing and implementing electronic textbooks